How do relatives cope with eating disorders? Results from an Italian multicentre study. Issue 5 (29th September 2016) - Fiorillo, Andrea; Sampogna, Gaia; Luciano, Mario; Del Vecchio, Valeria; Volpe, Umberto; Monteleone, Alessio Maria; Bruni, Antonella; Segura‐Garcìa, Cristina; Catapano, Francesco; Monteleone, Palmiero; Maj, Mario
ABSTRACT: Objective: This paper aims to: (1) describe coping strategies in relatives of patients with eating disorders (EDs); (2) analyze coping strategies according to the different EDs; (3) identify correlations between patients' clinical characteristics, relatives' socio‐demographic characteristics and coping strategies. Methods: Patients and their relatives consecutively attending three outpatient units for EDs at the Universities of Naples SUN, Salerno and Catanzaro were recruited. Coping strategies were assessed through the Family Coping Questionnaire for Eating Disorders (FCQ‐ED). It consists of 32 items, grouped into two factors: problem‐oriented ("seek for information", "positive communication") and emotion‐focused ("avoidance, " "collusion, " "coercion") strategies, plus one item on seeking for spiritual help. Results: Seventy‐two patients and 127 relatives were recruited. The most frequently reported coping strategies by relatives were seeking for information, positive communication, seeking for spiritual help; the first two coping strategies were positively correlated with the level of education of both patients and relatives. Mothers reported avoidance less frequently than other relatives. Relatives of patients with BN reported collusion and coercion more frequently compared to relatives of patients with AN. Discussion: This report represents an initial attempt to understand the complex relationship among clinical, social and personal variables involved in the development of coping strategies. © 2016 Wiley Periodicals, Inc.(Int J Eat Disord 2017; 50:587–592)